PREVALÊNCIA E FATORES ASSOCIADOS À DOR PÉLVICA CRÔNICA EM MULHERES DE SÃO LUÍS - MA - Coelho, Leidyane Silva Caldas (2010)
BACKGROUND: Chronic pelvic pain (CPP) is a debilitating disease and highly prevalent, with great impact on quality of life and productivity, and significant costs to health services. OBJECTIVE: To estimate the prevalence of CPP and the factors associated with women in Sao Luís- MA. METHODS: A study cross-sectional was conducted during one year in São Luís with 1.470 women over 14 years and had already had menarche. We used a systematic sampling process. Women were taken from homes of order 3, which corresponded to interview women in a house, jumping two places again, and interview the women of the next house, and so on until we get the sufficient number of interviews, pre-written in the sizing sample. The choice of the neighborhoods studied was conducted by random drawing of maps of the neighborhoods. The instrument of data collect was a questionnaire completed by the interviewer. The quantitative variables were compared using unpaired t test after confirmation of normal distribution by Kolmogorov-Smirnov test, while Fisher's exact test or chi-square tests were used to analyze qualitative variables. We selected the significant variables identified (P<0.10). After that, values of 0 or 1 were given for the absence or presence of CPP. A logistic regression was used to identify the significant independent variables and to estimate the simultaneous impact of these factors on assessment of CPP and the results were expressed by OR and 95%IC, considering P<0.05. RESULTS: CPP prevalence was 19.3%. On logistic regression, the factors independently associated with CPP were: abdominal surgery (OR 33.02, 95%CI [16.8-64.7]), dyspareunia (OR 5.0, 95%CI [3.0-8.3]), dysmenorrhea (OR 2.6, 95%CI [ 2.0-3.5]), alcoholism (OR 1.7, 95%CI [1.3-2.2]), headache (OR 2.2, 95%CI [1.7-2.9], low back pain (OR 2.2, 95%CI [1.7-2.9]), coffee intake (OR 0.18; 95%CI [0:13 to 0:25]); incision (OR 200, 95%CI [110-350]), transverse incision (OR 18, 95%CI [12-28]), section (OR 160, 95%CI [96-270]), smoking (OR 1.7, 95%CI [1.2-2.5]), pelvic inflammatory disease (OR 2.7, 95%CI [1.9-3.8]), abdominal distension (OR 1.5, 95%CI [1.0-2.3] ) symptoms of bladder irritation (OR 0.77, 95%CI [0.59-1.0]) and illicit drugs (OR 3.4, 95%CI [0.90-13]). CONCLUSION: The prevalence of CPP is high and is associated with abdominal surgery, cesarean section, longitudinal and transverse incisions, dyspareunia, dysmenorrhea, alcoholism, headache and back pain.